The Blood Brain Barrier and its Role in Alzheimer's Therapy: An Overview - Jakki, Satya L.; Senthil, V.; Yasam, Venkata Ramesh; Chandrasekar, M.J.N.; Vijayaraghavan, C. (Current Drug Targets, 2018)
Background: Alzheimer's disease (AD) is the most frequent age related neurodegenerative disorder. It represents 70% of all dementia. Millions of people have been affected by AD worldwide. It is a complex illness characterized pathologically by accumulation of protein aggregates of amyloid and neurofibrillary tangles containing hyperphosphorylated neuronal tau protein. AD requires drugs that can circumvent the blood–brain barrier (BBB) which is not a simple physical barrier between blood and brain, but acts as an iron curtain, allowing only selective molecules to enter the brain. Unfortunately, this dynamic barrier restricts transport of drugs to the brain; due to which, currently very few drugs are available for AD treatment. Objective: The present review focuses mainly on strategies used for administration of drug to the CNS by-passing BBB for the treatment of AD. Results: Many studies have proved to be effective in overcoming BBB and targeting drugs to CNS by using different strategies. Here we have discussed some of the most important drug permeability and drug targeting approaches. Conclusion: In conclusion, concentrating solely in development of drug discovery programs is not enough but it is important to maintain balance between the drug discovery and drug delivery systems that are more specific and effective in targeting CNS of AD patients.
Keywords: AD treatment